If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 2) + -4 = 0 Reorder the terms: 5(2 + 3x) + -4 = 0 (2 * 5 + 3x * 5) + -4 = 0 (10 + 15x) + -4 = 0 Reorder the terms: 10 + -4 + 15x = 0 Combine like terms: 10 + -4 = 6 6 + 15x = 0 Solving 6 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 15x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 15x = 0 + -6 15x = 0 + -6 Combine like terms: 0 + -6 = -6 15x = -6 Divide each side by '15'. x = -0.4 Simplifying x = -0.4
| -32-12x=2x+8 | | 3x^2-14x-56=0 | | 3(n-5)=8+4n | | 0=x^2-5x+14 | | 0=x^2-x+5 | | 50*2+150*2= | | x(2+5x)=0 | | 20*15*8= | | 0+x^2=2x-8 | | 42*3*4= | | 42*11*10= | | 6*36*6= | | -16=8(6q-2) | | 48*8= | | 2(2s+1)=50 | | 56*7= | | -108=9(9r-3) | | 5(8g-2)=30 | | 9=3(2s-5) | | 2(5d-5)=-40 | | 4(3i+3)=24 | | 2(4v-2)=20 | | -18=3(2g-2) | | 2*3*150= | | 95=11-14y | | 48=9+3u | | 4=6u-2 | | 4+11k=103 | | 30*32*9= | | 6-3u=18 | | 12*3.14= | | -16=3z+5 |